Adaptation and psychometric evaluation of a Brazilian version of the CYRM-28 - Ferreira, Aurino Lima (2022)
Using a sample of 832 young people, between 13 and 25 years old, the present research examined the psychometric properties of a Brazilian adaptation of the Child and Youth Resilience Measure-28 (CYRM-28), a scale empirically derived from a threefactor resilience model that has been promising for cross-cultural research. To establish validation, we use Confirmatory Factor Analysis to determine whether the traditional three-factor structure and the original items of CYRM-28 are compatible with a Brazilian sample. This was followed by tests of internal consistency by examining Cronbach’s alpha and convergent validity by testing correlations with the CD-RISC-10. The results led to a reduced version of 19 items distributed in three resilience factors. The findings are consistent with those observed in samples from other cultures and suggest that CYRM-19-Br is promising for use in resilience research in Brazil.